KONFLIK KEWENANGAN PENYIDIKAN DALAM PENANGANAN TINDAK PIDANA LINGKUNGAN HIDUP YANG DI LAKUKAN KOORPORASI - Boy Anggara; Imas Rosidawati Wiradirja; Syahrul Machmud (Iustitia Omnibus (Jurnal Ilmu Hukum), 2022)
The application of environmental criminal law is currently not optimal due to the absence of synchronization, or alignment, both structurally, substantially and culturally, in the criminal justice system from the police, prosecutors, courts and correctional institutions. The repetition of environmental crimes by individual and corporate legal subjects proves that there is disharmony between POLRI and PPNS investigators in tackling environmental crimes. This study aims to analyze how to resolve the conflict of investigation authority between Indonesian Police investigators and PNS investigators in enforcing environmental criminal law and how to harmonize the conflict of authority between POLRI investigators and PPNS. Normative juridical research methods or legal research libraries, sources of data used secondary data legal materials. The results of the analysis in this study indicate, the regulation of PPNS authority in environmental crimes is not in accordance with the criminal justice system based on the principle of lex specialis derogat legi generalis, the Criminal Procedure Code as a generalist and Law no. 32 of 2009 is the lex specialis of environmental crimes when the submission of the results of the investigation must go through the POLRI investigators. Meanwhile, the authority of POLRI investigators in Law Number 32 year 2009 is not clearly regulated. Keywords : Authority, Investigator, the environment